A U.S. Survey of Sexual Harassment in Ophthalmology Training Using a Novel Standardized Scale - Scruggs, Brittni A.; Hock, Lauren E.; Cabrera, Michelle T.; Wang, Kai; Oetting, Thomas A.; Abràmoff, Michael D.; Shriver, Erin M. (Journal of Academic Ophthalmology, 2020)
Objective This study aimed to assess the frequency and severity of sexual harassment toward ophthalmology trainees.Design Present study is an anonymous retrospective online survey.Participants U.S. ophthalmology residents and fellows participated in this study.Methods Sexual harassment comments directed toward University of Iowa ophthalmology trainees and faculty members were compiled. Statements were ranked by severity to develop the Iowa Verbal Sexual Harassment Scale. A brief, anonymous online survey incorporating the scale was sent to all United States ophthalmology residency program directors to distribute among trainees. Participants rated the prevalence, severity, and frequency of verbal and physical sexual harassment during training.Main Outcome Measures Response to the survey questions on the prevalence, severity, and frequency of reporting of verbal and physical sexual harassment in ophthalmology training.Results Among 112 respondents (59 men and 53 women), 72 (64.3%) experienced sexual harassment in the workplace from patients (86.8% of women vs. 44.1% of men; p < 0.0001, 95% confidence interval [CI]: 1.48–2.74). Trainees rarely experienced harassment by colleagues (10.7%) or supervisors (8.9%). Women experienced more severe and frequent sexual harassment compared with men, with 54.7% women and 30.5% men experiencing sexual harassment weekly (p = 0.013, 95% CI: 1.29–5.71). Unwanted touching was the most common physical harassment type. The trainees' threshold for reporting sexual harassment was higher than their worst actual experience (p< 0.0001, F(2,282) = 67.59). Few trainees formally reported verbal (6.3%) or physical sexual harassment (1.8%). Trainees most commonly responded to harassment by redirecting the harasser (67.9%). Only 33.9% of trainees rated their institution's sexual harassment training as helpful preparation for addressing harassment.Conclusion Most ophthalmology trainees experienced sexual harassment with almost all harassment coming from patients. Female trainees reported substantially greater severity and frequency of sexual harassment. There remains an unmet need for targeted response training in ophthalmology training programs.
Keywords: ophthalmology training; residency; fellowship; sexual harassment